Cardiac Pacemaker in Pregnancy: How to Manage? - Dian Paramita Kartikasari; Rerdin Julario (Universitas Airlangga, 2021)
Despite the increasing use of permanent cardiac pacemakers in a younger patient population, there are little data related to pregnancy. Normal physiologic alterations of pregnancy need to be taken into account in the management of the pregnant woman with a pacemaker in place. Similarly, gestational events including the potential for surgical intervention require a basic knowledge of pacemaker technology and monitoring. We present a case of a patient with junctional escape rhythm and was implanted pacemaker during pregnancy. A 24 years old women referred from obstetric outpatient clinic with asymptomatic bradycardia and cryptogenic stroke 2 years earlier. ECG shows sinus arrest with junctional escape rhythm. After multi-disciplinary discussion, team decided to implant double chamber pacemaker implantation. The pacemaker setting is adjusted to prepare caesarean section at 39 weeks gestation with delivery of an aterm infant. The postoperative course was uneventful. Pre-pregnancy pacemaker settings were re-established after the postpartum period. The current literature on managing pregnant patients with pacemakers is quite limited. Such patients require a multidisciplinary approach to care. Electromagnetic Interference (EMI) should be noticed.